Staged repair of thoracoabdominal aneurysm with infra‐renal elephant trunk graft. Issue 8 (1st July 2018) - Vargo, Patrick R.; Smolock, Christopher J.; Steffen, Robert J.; Parodi, Federico E.; Soltesz, Edward G.
Abstract: A patient with residual thoracoabdominal aortic aneurysm and chronic dissection extending into the branch iliac arteries underwent staged open and endovascular repair. Open repair of the reno‐visceral segment was performed with an "elephant trunk" trunk graft placed distally into a 12‐cm infra‐renal aorta. One month later, the patient underwent a successful completion endovascular aortic repair. This case demonstrates the utility of combining traditional and endovascular surgery to manage complex aortic pathologies.